Persepsi Masyarakat Islam terhadap Solusi Permodalan pada Lembaga Keuangan di Kecamatan Cempa Kabupaten Pinrang - Haeril Anwar; Rusnaena; Zainal Said (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
The lack of understanding of the Islamic community in financial institutions often causes problems in obtaining interest-free business capital solutions. Therefore it is necessary to understand people's perceptions of the capital of financial institutions. These problems can be identified by tracing the process of acquiring, interpreting, selecting, and organizing sensory information. The results of tracking people's perceptions of the capital of financial institutions will be analyzed using Islamic economic analysis.This research uses a qualitative approach and in collecting data using methods of observation, interviews, and documentation. Analysis of the data obtained from interviews, field notes, and other materials, was compiled systematically so that it was easily understood and elaborated in the form of quotations to find out how people's perceptions of capital in financial institutions as well as knowing capital concepts in the Cempa community with Islamic economic analysis.The results showed that: 1) Community perception The earthquake on capital issued by financial institutions is very helpful in improving the community's economy, especially in venture capital. 2) The concept of capital in the average earthquake community still uses conventional financial institutions that use the interest system that is prohibited by Islamic law. The Cempa community still uses the services of conventional financial institutions as a place for capital, because there are no Islamic financial institutions in the area. 3) Financial institutions in the Cempa community are quite evident from the results of interviews, the community uses the services of financial institutions as a place for business capital.